Arctigenin Inhibits Liver Cancer Tumorigenesis by Inhibiting Gankyrin Expression via C/EBPα and PPARα - Sun, Ying; Tan, Yu-jun; Lu, Zhan-zhao; Li, Bing-bing; Sun, Cheng-hong; Li, Tao; Zhao, Li-li; Liu, Zhong; Zhang, Gui-min; Yao, Jing-chun; Li, Jie (Frontiers in Pharmacology, 2018)
Burdock (Arctium lappa) is a popular vegetable in China and Japan that is consumed for its general health benefits. The principal active component of burdock is arctigenin, which shows a range of bioactivities in vivo and in vitro. Here, we investigated the potential anti-tumor effects of arctigenin using two human hepatocellular carcinoma (HCC) cell lines, HepG2 and Hep3B, and sought to elucidate its potential mechanisms of action. Our results showed that arctigenin treatment inhibited cell growth in both HepG2 and Hep3B cell lines (IC50 of 4.74 nM for HepG2 cells, and of 59.27 nM for Hep3B cells). In addition, migration, invasion, and colony formation by HepG2 cells were significantly inhibited by arctigenin. By contrast, treatment of Hep3B cells with arctigenin did not alter these parameters. Arctigenin also significantly reduced the levels of gankyrin mRNA and protein in HepG2 cells, but not in Hep3B cells. A luciferase assay indicated that arctigenin targeted the -450 to -400 region of the gankyrin promoter. This region is also the potential binding site for both C/EBPα and PPARα, as predicted and confirmed by an online software analysis and ChIP assay. Additionally, a co-immunoprecipitation (Co-IP) assay showed that binding between C/EBPα and PPARα was increased in the presence of arctigenin. However, arctigenin did not increase the expression of C/EBPα or PPARα protein. A binding screening assay and liquid chromatography–mass spectrometry (LC–MS) were performed to identify the mechanisms by which arctigenin regulates gankyrin expression. The results suggested that arctigenin could directly increase C/EBPα binding to the gankyrin promoter (-432 to -422 region), but did not affect PPARα binding. Expression of gankyrin, C/EBPα, and PPARα were analyzed in tumor tissues of patients using real-time PCR. Both C/EBPα and PPARα showed negative correlations with gankyrin. In tumor-bearing mice, arctigenin had a significant inhibitory effect on HCC growth. In conclusion, our results suggested that arctigenin could inhibit liver cancer growth by directly recruiting C/EBPα to the gankyrin promoter. PPARα subsequently bound to C/EBPα, and both had a negative regulatory effect on gankyrin expression. This study has identified a new mechanism of action of arctigenin against liver cancer growth.